Korelasi Penggunaan Media Quizizz dengan Motivasi Belajar Siswa pada Mata Pelajaran PAI - Irham Baniardhi; Maemunah Sa'diyah (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
This study aims to measure or analyze whether there is a significant correlation or relationship between the use of Quizizz media and the learning motivation of class VIII students in Islamic education subjects at SMPN 1 Bogor. This study uses a correlational quantitative research approach. The population in this study were all students of class VIII SMPN 1 Bogor as many as 296 students. The sample of this study was 25% of class VIII SMPN 1 Bogor, which was 74 students. Data was collected using a questionnaire and documentation techniques. While the data analysis technique uses statistical techniques, using product moment correlation to find the relationship between the two variables. The results of data analysis showed a positive correlation between the use of Quizizz media and the variable of student learning motivation with the value obtained by the value of rcount = 0.495. Thus, when compared to the value of rcount with the value of rtable, by taking a significance level of 5% and degrees of freedom n-2 = 74 – 2 = 72. Thus, the value of rcount > rtable = 0.495 > 0.232. Then based on testing the significance of the correlation coefficient using the t test formula, the tcount value is 4.833 and the ttable value at = 0.05 is 1.666, which means Ho is rejected and Ha is accepted. Keyword: Quizizz, Learning Motivation, Islamic Education